Training On Making Web Design (Bloggy) at SMK Negeri 8 Makassar: Pelatihan Pembuatan Desain Web (Bloggy) pada SMK Negeri 8 Makassar - Andi Harmin; Ida Ida; Muhammad Faisal (Yayasan Ahmar Cendekia Indonesia, 2023)
The purpose of this service is to provide additional knowledge to students which includes: basic knowledge of blog media, how to use free design templates, how to edit and use them as information media. To increase this knowledge, training participants are given basic knowledge and skills about: downloading free templates, editing designs in index files, displaying design results on localhost. The implementation of the service is carried out in several methods, namely: lectures, discussions and practical assistance. The results of the evaluation that we got during the training of community service activities, we can conclude that this community service program has been able to provide enormous and targeted benefits for Vocational High School students who are partners in this activity. This form of training is very effective in providing refresher and insight as well as additional knowledge in the field of web-based computers. So that it can improve the understanding and abilities and skills of students in partners so that they can be added to the partner curriculum. Abstrak Tujuan pengabdian ini dilaksanakan adalah memberikan pengetahuan tambahan kepada para siswa/i yang meliputi: pengetahuan dasar tentang media blog, cara memanfaatkan free design template, cara mengedit dan pemanfaatannya sebagai media informasi. Untuk meningkatkan pengetahuan tersebut peserta pelatihan diberikan materi pengetahuan dan keterampilan dasar tentang: download free templates, edit design pada file index, menampilkan hasil design dalam localhost. Pelaksanaan pengabdian dilaksanakan pada dengan beberapa metode, yaitu: ceramah, diskusi dan pendampingan praktek. Hasil evaluasi yang kami dapatkan selama pelatihan kegiatan pengabdian kepada masyarakat, dapat kami simpulkan bahwa program pengabdian kepada masyarakat ini telah mampu memberikan manfaat yang sangat besar dan tepat sasaran bagi siswa/i Sekolah Menengah Kejuruan yang menjadi mitra dalam kegiatan ini. Bentuk pelatihan ini sangat efektif dalam memberikan penyegaran dan wawasan serta pengetahuan tambahan dalam bidang komputer berbasis web. Sehingga dapat meningkatkan pemahaman dan kemampuan serta keterampilan siswa/i pada mitra sehingga bisa menjadi tambahan dalam kurikulum mitra.